Customer Loyalty in Coffee Shop: Literature Review and Condition for The Future - Pesoa, J.A.; Kristyanto, B.; Dewa, P.K. (Universitas Atma Jaya Yogyakarta, 2020)
The Corona Virus 2019 or Covid-19 outbreak has caused a global panic that is fatal. Various sectors have been affected. The coffee industry sector has also been affected by Covid-19. Losing customer loyalty is a threat to coffee industry entrepreneurs. This study has the purpose of measuring Customer Loyalty and a way to prevent the coffee shops from losing customers during the Covid-19 pandemic. This purpose is divided into two-stage. The first stage is to identify what factors affect customer loyalty and the relationship before the pandemic. The second stage is to test these factors during the Covid-19 pandemic in the context of the coffee shop business area. The second stage will be done for future study purposes. To support the first stage, the author divided it into two steps. First: summarize the factors that affect customer loyalty in the coffee shop business area. The second: is to build a relationship of the factors that affected customer loyalty based on the summarized factor in the first step. The results of this study show that customer satisfaction and trust have a direct effect on customer loyalty. Moreover, these factors can be a suitable mediation for others factors influencing loyalty. Besides that, service quality and price fairness can affected both mediation factors. Moreover, every existing factor also has an important role because these factors influence and support each other in creating Customer Loyalty.